Social Comparison as a Tool to Promote Residential Water Conservation - Schultz, Wesley; Javey, Shahram; Sorokina, Alla (Frontiers in Water, 2019)
Many regions around the world experience both chronic and intermittent needs for residents to reduce their water consumption. Recent advances in water metering infrastructure offer opportunities to provide customers with detailed feedback about their consumption, but research in behavioral science suggests that feedback by itself is not enough to motivate conservation. The current empirical work builds on previous studies showing the ability of an augmented feedback approach to promote reductions in residential water consumption, and extends previous research by exploring the variability in responses to this feedback. A sample of Sacramento customers was provided with printed home water reports in which they could see their household water consumption compared with similar homes in their area. The results showed that households that received the report used 8.5% less water in the subsequent six months than did similar households that did not receive the printed reports. Additional analyses showed that the effect was particularly strong for high-consuming households, and that the discrepancy between household consumption and similar homes influenced the amount of water savings.